The impact of honey consumption on cardiorespiratory fitness and some physical abilities of Al-Shatra Sports Club footballer - Hussein Khalaf, Aqeel; Hasan Tuaimah, Mohammed (Journal of Neonatal Surgery, 2025)
The healthy nutrition and how to give it has become one of the important aspects that must be focused on and given correctly along with training programs, especially since most athletes are always looking for what may enable them to compete and help them achieve the best they can and it is obvious that the best and most effective ways to develop sports capabilities through good training and ideal nutrition with that in order to achieve the best results from the training program may be worth thinking about proper nutrition that contains Natural foodstuffs Therefore, the interest in supplying players with food that suits the type of trait to be developed, as it can contribute, along with good training methods based on scientific foundations, to the development of the player's physical and physiological potential, as honey is a food rich in natural sugars, and that the importance of research lies in the need for players, in particular, to obtain energy-rich food in order to obtain the best levels or better performance, and for that the researchers prepared a diet consisting of honey And to identify its impact on the level of cardiorespiratory and physical fitness of the players of Al-Shatra Football Club in Applicants, and the problem of research arises in the lack of data of an accurate scientific nature for nutrition needed by coaches in order to contribute to the development of their training programs so that he can with knowledge of the changes that occur to the players through the application of the vocabulary of the training unit, and that the efficiency of preparing athletes depends heavily positively on functional, chemical and physical changes in the face of fatigue and this can only be achieved by regulating the relationship between the rationing of the training load for effectiveness with the organization of the nutritional aspect, either The most important objectives of the research were to identify the effect of eating honey on the level of cardiorespiratory fitness and some physical abilities of football players, either the most important hypotheses there are statistically significant differences between the two groups (experimental - control) and in favor of the experimental group in the level of cardiorespiratory fitness and physical capabilities of football players, either the most important conclusions were eating honey before physical exertion has a positive effect in delaying fatigue in football players.